The Applicability of Thromboelastography in Acute Ischemic Stroke: A Literature Review - Pîrlog, Bianca O.; Grotta, James C. (Seminars in Thrombosis and Hemostasis, 2022)
Acute ischemic stroke (AIS) due to cerebral artery occlusion is often treated by thrombolytics or antithrombotic drugs. Thromboelastography (TEG) is a noninvasive test that provides a dynamic overview of the coagulation process. TEG may help guide thrombolytic and antithrombotic therapy in AIS. This article aims to highlight the potential use of TEG in AIS patients by reviewing available studies. We conducted a literature review, including PubMed and Cochrane library databases. The following keywords were used to find relevant studies: thromboelastography, TEG, acute ischemic stroke, stroke, coagulopathy, antiplatelet, and anticoagulant treatment. We identified 142 papers and after abstract review, we included 24 studies in this report. TEG identified a hypercoagulable state in AIS patients represented by short R, K, and greater α angle in all papers included. Modification of TEG parameters induced by intravenous thrombolysis was inconsistent but prolonged lysis (increased LY30) and weaker clots (lower maximum amplitude) were most frequent. TEG detected hypo-coagulopathy induced by dual antiplatelet therapy as well as antiplatelet drug resistance, with ticagrelor and aspirin having greater inhibition of platelet activity. A prolonged R-value seems to be the most reliable TEG parameter in detecting the anticoagulant effect of factor Xa inhibitor treatment. TEG might represent a useful point-of-care test for emergency decision-making in AIS patients and a tool for individualized treatment options. This hypothesis needs validation in a large cohort of prospectively studied AIS patients.
Keywords: thromboelastography; TEG; acute ischemic stroke; coagulopathy; antiplatelet treatment; anticoagulant treatment